Simulations of Asymmetric Flow Structures around a Moving Sphere at Moderate Reynolds Number. (15th July 2015) - Young, D.-L.; Wu, C.-S.; Wu, C.; Lin, Y.-C.
Abstract : The evolution of asymmetric leeward-side flow structures around a moving sphere in the viscous flow is investigated. Simulations are carried out to investigate the variations of vortex-ring system at the moderate Reynolds number. A parallel laboratory experiment is undertaken in this study. The sphere travels a certain distance at constant speed and then stops to collide with a wall. The motion of moving sphere in fluid is described by the hybrid Cartesian immersed boundary method. Drag forces behind the moving sphere are extremely substantial as the solid body falls through viscous fluid for comprehending the formation of wake flow. The dynamic behavior consists of growth and breakup of the vortices which depend on two specific moderate Reynolds numbers. The onset of physical instability in the wake is obviously affected at the Reynolds number of 800. The generated vortex-ring system rolls upward to compact the primary vortex ring and interact with the secondary vortex. An asymmetric generation of the pairs of vortices is developed since the physical instability effect leads to shed in the wake with the increasing Reynolds number. The results from numerical simulations are also conducted to exhibit good comparison with those from the laboratory experiment.